Recycling the Aura - Benjamin with Deleuze - Čekić, Jovan (Belgrade Journal of Media and Communications, 2012)
Is it possible today to ask again Benjamin’s question about the work of art? Is it not true that the entire character of art has radically changed with the emergence of digital technology? The flux of images and pictures is the end of territorialisation. Instability is the rule, the rule of the society of control. But in this instability, the system constantly reconstructs and recycles the aura from its disintegrated fragments. It also stimulates subversive and critical practices while glorifying technoinnovation and experiment. But art is only one special case of this recycling of the aura which appears in the most diverse forms and manifestations. Art should therefore no longer be thought of as one enclave among others in the capitalist machine. It may cut across all enclaves and create clusters of resistance, vectors of liberation.
https://katalog.adlr.link/Record/ai-53-127582